The effects of abrupt dietary changes on the hindgut environment of the horse - Jones, Jessica Ashley (Kansas State University, 2015)
Abrupt dietary changes increase a horse’s risk for developing gastrointestinal diseases, such as colic or laminitis. Understanding the impact of various feeds and feeding practices on feeding behavior and gastrointestinal function creates a whole-animal perspective that allows for a more holistic interpretation of the effects of abrupt dietary changes on the hindgut environment. Unfortunately, few reports exist that have examined the effects of abrupt dietary changes in the horse. This study was designed to determine the effects of various abrupt dietary changes on the hindgut environment. In 4 sequential experiments, horses were exposed to an abrupt change from a baseline ration to a complete pelleted diet, an abrupt change from a baseline ration to a 100% grass hay diet, an abrupt change from a prairie hay ration to an alfalfa hay ration, and an abrupt change from a baseline ration to a large concentrate meal. These dietary challenges were chosen to mimic real-world scenarios that horse owners are likely to encounter. These experiments were arranged into a longitudinal trial in which the effects of the abrupt dietary change on cecal and fecal pH, total lactate and volatile fatty acid (VFA) concentrations, cecal lactate-utilizing bacterial populations, and fecal dry matter (DM) were compared to values obtained while horses were consuming the baseline diet. In the first experiment, decreased cecal (P ˂ 0.0001) and fecal (P ˂ 0.0001) pH values combined with increased cecal total lactate (P ˂ 0.001) and fecal VFA concentrations (P ˂ 0.0001) indicate that the abrupt change to a complete pelleted diet disrupted the stability of the hindgut environment. Because cecal pH values were below 6.0, this dietary challenge may be significant enough to elicit subclinical fermentative acidosis and, thereby, increase colic risk. The dietary change to grass hay had little impact on the hindgut environment, as pH, total lactate, and VFA concentrations remained stable (P ≥ 0.05). In general, horses may well tolerate an abrupt increase in the fibrous component of the diet and the elimination of concentrate, a dietary shift that presents a more natural diet to the horse. The abrupt change to alfalfa hay elicited alterations in cecal pH (P ˂ 0.01), total lactate (P ˂ 0.0001) and VFA concentrations (P ˂ 0.05), and lactate-utilizing bacterial populations; however, fecal parameters varied little in response to the dietary change (P ≥ 0.05), indicating that the distal hindgut may be more tolerant to abrupt changes in forage sources than the cecal environment. Here, the potentially adverse shifts in cecal parameters indicate that an abrupt change in hay type and quality alters the fermentative environment of the proximal hindgut and may increase a horse’s risk for gastrointestinal disease. Similarly, the abrupt introduction of a large concentrate meal elicited a decrease in cecal pH (P ˂ 0.005) along with increases in total lactate (P ˂ 0.001) and VFA concentrations (P ˂ 0.05) in the cecum that were consistent with previously reported experiments in which horses were presented with large increases in dietary concentrates. Notable shifts in lactate-utilizing bacterial growth curves were also observed. Overall, these results provide evidence of environmental alterations in the equine hindgut that support epidemiological reports that associate abrupt changes in the amount and type of concentrate, hay type and quality, and forage:concentrate ratio with increased risk for gastrointestinal disease in horses.
Keywords: Cecum; Dietary change; Equine; Hindgut; Lactate-utilizing bacteria; Animal Sciences (0475)